Empirically Derived Test Specifications for the Certified Rehabilitation Counselor Examination: Revisiting the Essential Competencies of Rehabilitation Counselors. (October 2019) - Leahy, Michael J.; Chan, Fong; Iwanaga, Kanako; Umucu, Emre; Sung, Connie; Bishop, Malachy; Strauser, David
The purpose of this article is to examine the results of the certified rehabilitation counselor (CRC) knowledge validation study conducted in collaboration with the Commission on Rehabilitation Counselor Certification (CRCC). The research design for the present study includes both descriptive and ex post facto approaches. Three hundred ninety-four CRCs completed the Knowledge Validation Inventory–Revised (KVI-R) survey. Factor analysis results revealed six knowledge domains: (a) rehabilitation and mental health counseling, (b) employer engagement and job placement, (c) case management, (d) medical and psychosocial aspects of chronic illness and disability, (e) research methodology and evidence-based practice, and (f) group and family counseling. The findings of this study provide important information for CRCC to examine and develop test and item specifications that will guide future versions of the CRC examination. The findings also inform the description of the knowledge base underlying the practice of rehabilitation counseling and contribute further empirical evidence regarding the knowledge domains identified in this replication and extension of the previous study completed in 2012.